JENIS DAN POTENSI TUMBUHAN OBAT PADA KAWASAN HUTAN ADAT GUNUNG SEMARONG KECAMATAN TAYAN HULU KABUPATEN SANGGAU - bertus, Al; Dewantara, Iswan; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2015)
Indonesia Forest has a natural resources which many diverse regione specially in indigenous Forest of Mount Semarong were located in the district of Hulu Tayan Sanggau which have a diversity of flora is more high including the medicinal plants. The purpose of this study is to discoverthe type and potency of medicinal plants in the forest area of Indigenous forest of Mount Semarong. The method used in this research using a descriptive interview and to discover the potential of the indigenous Forest of Mount Semarong using multiple plots arranged in purposive sampling with a broad swath of the observations of 20 x 20 by 50 plot observations. Results of interviews recorded 40 species of medicinal plants with 30 family. However, from the results of field observations found only 33 species of medicinal plants. Of the 33 species recorded was found six species of medicinal plants are cultivated and 7 types that are not found in the observation plots. The results of analysis of vegetation found in the area of indigenous forest of Mount Semarong recorded 20 species of medicinal plants. Down at the level of individual plants having the highest value as many as 640 individuals with a percentage (34%), out second at Stake level as much as 567 people with a percentage (31%), ranked third in the pole rate of 420 individuals with a percentage (23%) and lowest comes out at a rate of as many as 222 individuals trees with percentage (12%). Keywords : Indigenous Forest Region, Mount Semarong, Species, Potential medicinal plants.